The Influence of Non-Performing Loans and Cash Turnover on Liquidity in Banking Companies Listed on the Idx For the 2017-2020 Period - Inayati, Siti Reuni; Ihsan, Sahrul (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
This research aimed to analyze the impact of nonperforming loans and cash turnover on liquidity in financial institutions included in the IDX between 2017 and 2020. The sample for this research consisted of 46 financial institutions. Purposive sampling was utilized to choose 13 companies for a four-year study period (2017-2020). Information was gleaned from the Indonesia Stock Exchange's website (www.idx.co.id) and downloaded for analysis. Results from certain studies suggest that neither cash turnover nor non-performing loans have a direct impact on liquidity.